Stabilisation/solidification treatment and remediation [electronic resource] : advances in S/S for waste and contaminated land - Al-Tabbaa, Abir; Stegemann, Julia A.; International Conference on Stabilisation/Solidification Treatment and Remediation (2005 : University of Cambridge, United Kingdom) (Leiden : A.A. Balkema Publishers, 2005)
10